Innovation of Assistive Technologies in Special Education: A Review - Anna Felicia; Sabariah Sharif; W. K. Wong; Muralindran Marriappan (2014)
Assistive technologies in education have been rapidly expanding in recent years with the multiple of choices which are embedded in the school syllabus. Recently, the innovation has been penetrating schools worldwide more rapidly. This paper provides a critical discussion and review on the concepts of assistive technologies in education, applications, and research on the innovation. Central to the discussion is a better understanding of scientific usage of the technologies in schools. Assistive technologies further serves as a problem-solving tool or medium that enhanced learning via many factors such as critical thinking, multimodal learning and motivational approaches. The targeted goal of the paper, therefore, is to stimulate the discussion of assistive technologies as the innovation in education based on current research and practical applications.